PEMILIHAN SMARTPHONE TERBAIK PENUNJANG KEGIATAN AKADEMIS MENGGUNAKAN METODE BWM DAN PENGEMBANGAN AHP - Mochammad Iffan Zulfiandri; Hasbi Yasin; Sudarno Sudarno (Department of Statistics, Faculty of Science and Mathematics, Universitas Diponegoro, 2021)
Multi-Criteria Decision Making (MCDM) is a decision-making method to determine the best alternative from several alternatives based on several certain criteria. One of the alternative decision-making methods that can be used is the Best Worst Method (BWM) and the Analytical Hierarchy Process (AHP). BWM makes structured pairwise comparisons and AHP breaks down complex problems into hierarchical structures. One of the decision-making problems that can be solved by the BWM and AHP methods is the problem of choosing a smartphone. Smartphones are one of the most widely used Information and Communication Technology (ICT) devices by Indonesians. The use of smartphones as ICT devices has benefits for the academic community, especially as a means of supporting academic activities. However, various types and mereks of smartphones are circulating, making users confused about choosing the best smartphone according to their needs. Therefore, a reliable method is needed to make it easier for users to choose the best smartphone, especially in supporting academic activities, namely by using a combination of the BWM method and AHP development. The BWM method is used to calculate the optimal weight of the criteria and the AHP method that has been developed is used to calculate the alternative optimal weight based on the criteria. The combination of the two is used to calculate the final optimal weight for each alternative. The results of the calculation of the optimal weight of the criteria show that the RAM criterion has the highest weight, which is 0.290 and the Screen Size criterion has the lowest weight, which is 0.047. The final result obtained is a smartphone type OPPO Find X2 with a final optimal weight of 0.153 to be the best alternative among other alternatives. Keywords: Multi-Criteria Decision Making (MCDM), Best Worst Method (BWM), Analytical Hierarchy Process (AHP), Information and Communication Technology (ICT), Smartphones, Academic Activities